CURRENT PROFILE OF PEFC CHAIN OF CUSTODY CERTIFIED COMPANIES IN ROMANIA - Cristian Mihai ENESCU; Andrei APĂFĂIAN; Aureliu Florin HĂLĂLIȘAN; Dan Răzvan Eugen PUICEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
PEFC is one of the most common certification schemes in forestry worldwide. The aim of this paper was to highlight the profile of the PEFC Chain of Custody certified companies from Romania. Data available in December 2018 on the official website of PEFC were taken into consideration. Until present, 43 PEFC CoC certified companies were recorded in Romania, more than half holding an individual certificate. The certified companies are located in fifteen counties plus Bucharest, one quarter of them being based in the capital city. 60% of the valid CoC certificates in Romania were issued only by two certification bodies. As regards the product category, the number of the companies involved in paper-related activities is almost equal with the companies acting in wood industry. Even though Romania is a country well known for its forest resources and its wood industry, PEFC certification is not very well represented. But, by taking into account that PEFC national certification system was endorsed in mid-summer 2018, it might happen very soon that PEFC (both FM and CoC) will gain more interest in Romania.